The role of proestrus on fertility and postovulatory uterine function in the cow - Binelli, M. (2014)
Modern protocols to synchronize ovulations for timed artificial insemination and timed embryo transfer that include manipulations in the proestrus period (i.e., between luteolysis and estrus) affect fertility in cattle. Specifically, stimulating pre-ovulatory follicle growth and exposure to estrogens after CL regression increase the proportion of cows pregnant and decrease late embryo mortality. Such effects may be due to both preovulatory actions of estrogens and post-ovulatory actions of progesterone, as concentrations of the later hormone may be changed in response to manipulations conducted during proestrus. In the first portion of this paper we describe strategies used recently to manipulate the proestrus period in protocols for synchronization of ovulation, and to present evidence of their effects on fertility. Manipulations of timing and prominence of sex steroids during the proestrus and early diestrus that affect fertility may act on targets such as the endometrium. This tissue expresses receptors for both estrogens and progesterone and these hormones change endometrial function to support conceptus growth and pregnancy maintenance. However, specific cellular and molecular mechanisms through which fertility is affected via manipulations of the proestrus are poorly understood. In the second portion of this paper we describe a well-defined animal model to study changes in endometrial function induced by manipulations conducted during the proestrus. Such manipulations induced endometrial changes on sex steroid receptors expression, cell proliferation, oxidative metabolism and eicosanoid synthesis in the uterus, but not on glucose transport to uterine lumen. In summary, evidence is accumulating to support a positive role of increasing duration and estrogen availability during the proestrus on fertility to synchronization protocols. Such positive effects may be through changes in endometrial function to stimulate conceptus growth and survival.